Ru-Catalyzed Domino C-4 Alkylation and Hydroxylation of Pyrazolones Using Alcohols via Borrowing-Hydrogen Catalysis - Jadhav, Pramod M.; Jamdade, Akash Bandu; Gnanaprakasam, Boopathy (Synlett, 2025)
Herein, we developed a domino approach for the C-4-functionalization of pyrazolones, which includes sequential C-4 alkylation and C–H hydroxylation with alcohols to achieve C-4-substituted pyrazolones and pyrazoles via borrowing-hydrogen catalysis. The method is successfully facilitated in the presence of RuH2CO(PPh3)3 catalyst and sodium hydroxide as a base. Notably, this approach has been well validated with the 16 examples of C4-substituted pyrazolones with hydroxylated products and 14 examples of substituted pyrazoles, generating water as the sole, environmentally benign byproduct.
Keywords: Domino reaction; Ru-catalyst; Borrowing alkylation; C–H hydroxylation; Pyrazolones; Pyrazoles